Assessing the influence of hard and soft infrastructure on perceived destination competitiveness : Perspective from visitors in Sarawak - Chan, Wei Chiang; Wan Hashim, Wan Ibrahim; Lo, May Chiun; Abang Azlan, Mohamad (2022)
Tourism is one of the rapid growing economic sectors in the world. Destination competitiveness became imperative aspect for every country as it determines the tourism revenue of the country. Infrastructure is one of the determinants of destination competitiveness. There are two kind of infrastructure namely hard infrastructure and soft infrastructure. The current study investigated the impact of hard infrastructure (transportation, telecommunication, accommodation) and soft infrastructure (government tourism policy, health services and safety and security) to perceived destination competitiveness from tourists’ point of view. The study was conducted based on quantitative research. A PLS-SEM analysis was performed by using WarpPLS. The result indicated that transportation, accommodation, and health services have significant relationship with perceived destination competitiveness. This study is expected to benefit the policy makers and industry players in terms of decision making. Besides, this study will equip more literature and evidence for the scholars to perform further study in the field.